A 3D Bioprinted in vitro Model of Neuroblastoma Recapitulates Dynamic Tumor‐Endothelial Cell Interactions Contributing to Solid Tumor Aggressive Behavior. Issue 23 (29th May 2022) - Ning, Liqun; Shim, Jenny; Tomov, Martin L.; Liu, Rui; Mehta, Riya; Mingee, Andrew; Hwang, Boeun; Jin, Linqi; Mantalaris, Athanasios; Xu, Chunhui; Mahmoudi, Morteza; Goldsmith, Kelly C.; et al.
Abstract: Neuroblastoma (NB) is the most common extracranial tumor in children resulting in substantial morbidity and mortality. A deeper understanding of the NB tumor microenvironment (TME) remains an area of active research but there is a lack of reliable and biomimetic experimental models. This study utilizes a 3D bioprinting approach, in combination with NB spheroids, to create an in vitro vascular model of NB for exploring the tumor function within an endothelialized microenvironment. A gelatin methacryloyl (gelMA) bioink is used to create multi‐channel cubic tumor analogues with high printing fidelity and mechanical tunability. Human‐derived NB spheroids and human umbilical vein endothelial cells (HUVECs) are incorporated into the biomanufactured gelMA and cocultured under static versus dynamic conditions, demonstrating high levels of survival and growth. Quantification of NB‐EC integration and tumor cell migration suggested an increased aggressive behavior of NB when cultured in bioprinted endothelialized models, when cocultured with HUVECs, and also as a result of dynamic culture. This model also allowed for the assessment of metabolic, cytokine, and gene expression profiles of NB spheroids under varying TME conditions. These results establish a high throughput research enabling platform to study the TME‐mediated cellular‐molecular mechanisms of tumor growth, aggression, and response to therapy. Abstract : Manufacturing a biomimetic, highly tunable, 3D in vitro model using embedded bioprinting strategy (A) in combination with neuroblastoma spheroids and human endothelial cells (B). The established tumor microenvironment model can serve as a high‐throughput research enabling platform to generate insights into the neuroblastoma tumor‐endothelial cell interactions, as well as tumor growth and aggression at the cellular and molecular levels (C‐D).